Interactions between p-Akt and Smad3 in injured muscles initiate myogenesis or fibrogenesis - Dong, Yanjun (American Physiological Society, 2013)
In catabolic conditions such as aging and diabetes, IGF signaling is impaired and fibrosis develops in skeletal muscles. To examine whether impaired IGF signaling initiates muscle fibrosis, we generated IGF-IR(+/−) heterozygous mice by crossing loxP-floxed IGF-IR (exon 3) mice with MyoD-cre mice. IGF-IR(+/−) mice were studied because we were unable to obtain homozygous IGF-IR-KO mice. In IGF-IR(+/−) mice, both growth and expression of myogenic genes (MyoD and myogenin; markers of satellite cell proliferation and differentiation, respectively) were depressed. Likewise, in injured muscles of IGF-IR(+/−) mice, there was impaired regeneration, depressed expression of MyoD and myogenin, and increased expression of TGF-β1, α-SMA, collagen I, and fibrosis. To uncover mechanisms stimulating fibrosis, we isolated satellite cells from muscles of IGF-IR(+/−) mice and found reduced proliferation and differentiation plus increased TGF-β1 production. In C(2)C(12) myoblasts (a model of satellite cells), IGF-I treatment inhibited TGF-β1-stimulated Smad3 phosphorylation, its nuclear translocation, and expression of fibronectin. Using immunoprecipitation assay, we found an interaction between p-Akt or Akt with Smad3 in wild-type mouse muscles and in C(2)C(12) myoblasts; importantly, IGF-I increased p-Akt and Smad3 interaction, whereas TGF-β1 decreased it. Therefore, in muscles of IGF-IR(+/−) mice, the reduction in IGF-IR reduces p-Akt, allowing for dissociation and nuclear translocation of Smad3 to enhance the TGF-β1 signaling pathway, leading to fibrosis. Thus, strategies to improve IGF signaling could prevent fibrosis in catabolic conditions with impaired IGF signaling.